Wireless medical interface using zigbee and bluetooth technology - Mulyadi, Indra H. (Institute of Electrical and Electronics Engineers, 2009)
Since years, the using of telemedicine has increased although there are some technical issues related to standard and quality. In order to improve the telemedicine quality of service, a robust wireless connection between medical devices and telecommunication network is required. Unfortunately, many medical devices were developed without possibility to connect with telecommunication infrastructure. Due to this condition, a wireless medical interface has been developed. The interface has been implemented based on the advantages of ZigBee and Bluetooth technology. A new protocol has also been developed to enable robust communication between medical devices and telecommunication infrastructure. The interface has been tested to transfer the medical data from vital sign medical devices to a data processing system through wireless network. Measurement result shows that the interface is able to be used in transferring medical data from multi medical devices within range of 10 m with some interference sources.